Outage performance of underlay cognitive radio networks over mix fading environment - Nguyen Hong Nhu; Cuu Ho Van; Van-Duc Phan; Tan N. Nguyen; Miroslav Voznak; Jaroslav Zdralek (International Journal of Electrical and Computer Engineering (IJECE), 2021)
In this paper, the underlay cognitive radio network over mix fading environment is presented and investigated. A cooperative cognitive system with a secondary source node S, a secondary destination node D, secondary relay node Relay, and a primary node P are considered. In this model system, we consider the mix fading environment in two scenarios as Rayleigh/Nakagami-m and Nakagami-m/Rayleigh Fading channels. For system performance analysis, the closed-form expression of the system outage probability (OP) and the integral-formed expression of the ergodic capacity (EC) are derived in connection with the system's primary parameters. Finally, we proposed the Monte Carlo simulation for convincing the correctness of the system performance.